2021
DOI: 10.3390/ijerph18137137
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Gaming Disorder in the Effect of Narcissism on Happiness in Children

Abstract: We aimed to determine the relationship between gaming disorder, narcissism, and happiness levels of children between the ages of 9 and 15. This study was based on the compensation theory. The sample consists of 461 boys who continue their education in public schools in Istanbul. In the study, a mixed research design, which nests qualitative data into quantitative, was used. In addition to the scales and sociodemographic form, the Draw-a-Person test was also used to better understand children’s inner world. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…As long as playing games is kept under control, it can positively affect students, providing fun, stress relief, relaxation, and socializing with people from different periods of life. Otherwise, adverse effects on young people arise when gaming becomes excessive and addictive [42].…”
Section: The Internet Addiction In Turkish Adolescents and Its Contributorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As long as playing games is kept under control, it can positively affect students, providing fun, stress relief, relaxation, and socializing with people from different periods of life. Otherwise, adverse effects on young people arise when gaming becomes excessive and addictive [42].…”
Section: The Internet Addiction In Turkish Adolescents and Its Contributorsmentioning
confidence: 99%
“…However, the use of the internet for educational purposes has become widespread during the COVID-19 pandemic period [47]. Therefore, young people's use of the internet for educational purposes sometimes leads them to use it for other purposes, such as playing online games and socializing [42]. Similarly, it is also seen that young people become internet or online game addicts over time under the pretext of study [48,49].…”
Section: Self Esteem Daily Internet Usage and Internet Addictionmentioning
confidence: 99%
“…However, it was observed that the level of this relationship was low The digital games that students play mostly to socialize with friends or family members, reduce stress, keep the mind active or dive into a different world cause behavioral addiction as well as many biological and psychological disorders (Ko & Yen, 2020). Narcissism, one of these disorders, is a phenomenon that increases with gaming disorder (Çevik et al, 2021). Di Blasi et al (2020) concluded that narcissism is associated with game addiction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to behavioral addiction, digital games also cause many biological and psychological disorders, especially in young people in development and adolescence (Ko & Yen, 2020). Narcissism is one of these behavioral disorders and increases with internet gaming disorder (Çevik et al, 2021). The spread of social media has also been one of the factors that triggered narcissism very quickly (Balci & Gargalik, 2020).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Therefore, children may reflect what they see in their families’ behaviors and become reflections of their parents somehow. Individuals, who take the ethical values of their family, live with these values throughout their lives [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Children, who see equality in the distribution of roles of the mother and father, and support each other by solidarity, will adopt them in their adult life [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%